Hermeneutika Sufistik Surah al-Ikhlāṣ dalam Tafsir Aḥmad Yāsīn Asmunī - Ma’arif, Umayyatul Haritsah; Wahyu Nur Oktavia (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
This article aims to examine Aḥmad Yāsīn Asmunī’s interpretation of Surah al-Ikhlāṣ through the combined analytical lenses of Sufi hermeneutics and critical sociolinguistics. Asmunī, a contemporary Javanese scholar, situates the surah within intertwined linguistic and spiritual frameworks. His exegesis emphasizes ma‘rifat Allāh (knowledge of God) as a form of inner paradise and interprets al-ṣamad as the absolute locus of human dependence. The analysis demonstrates that his reading transcends literal meaning by embedding Sufi notions of transcendence and spiritual resistance, particularly in his treatment of lam yalid wa lam yūlad and wa lam yakun lahu kufuwan aḥad, which counter anthropomorphic conceptions of God. From a critical sociolinguistic perspective, Asmunī’s tafsīr operates not merely as a theological explanation but as a discursive strategy that contests hegemonic narratives. It responds to polemics raised by polytheists as well as theological claims in Jewish and Christian traditions. The study argues that his interpretive method illustrates a dual linguistic function of the Qur’an: shaping spiritual consciousness while simultaneously constructing ideological resistance. By integrating linguistic precision with Sufi hermeneutics, Ahmad Yāsīn’s work contributes significantly to the intellectual landscape of Nusantara tafsīr and highlights the dynamic interplay between language, power, and spirituality in the reception of the Qur’an.